EVALUATION THE COACHING PROGRAM OF TENNIS TEAM OF BANGKA BELITUNG PROVINCE IN PON XIX WEST JAVA 2016 - Kurnia Tahki; Mulyana Mulyana; James Tangkudung (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
Coaching in every sport should be a planned and continuous process so as to achieve the expected goal. A well-developed and executed coaching program is also capable of being evaluated in order to make improvements over time. The purpose of this research is to get information about coaching program of Pelatda’s TennisTeam of Bangka Belitung Province in PON XIX West Java 2016. This research was conducted in Jakarta, Bandung and Bangka Belitung from February to December 2016, before and after PON XIX West Java 2016.This evaluation research using qualitative method with evaluation model Context, Input, Process, Product or CIPP according D.Stufflebeam (2002). Data collection was done by interview, observation, documentation study and interactive. Data sources in this research are: Youth and Sports Office of Bangka Belitung Province, KONI of Bangka Belitung Province, coaches of pelatda, PELTI of Bangka Belitung Province.The results concluded that: (1). The evaluation component of context stage is considered sufficient (59.26%). (2). The evaluation component of input stage is considered sufficient (65,63%). (3). The evaluation component of process stages is considered less (42.86%). (4). The evaluation component of product stage is considered to be very less (28,58%). Keywords: Evaluation, Coaching Program, Tennis Team of Bangka Belitung Province, PON XIX West Java 2016